20 años después del proceso de apertura económica: Más mercados con poca diversificación exportadora (2013)
In the early nineties, Colombia adopted a plan to open its economy aimed to modernize and diversify exports. The model distinguished itself for liberalizing markets and attracting foreign investment to Colombia. These policies diverged substantially from those in vogue till the late eighties -Import Substitution Industrialization (ISI)- that through protectionism and state aid achieved an important industrial development. Twenty years later exports increased six fold; however non-traditional products especially in the industrial sector, remain low enough to prevent an adequate participation in the globalized world.